Mecanismo de morte celular induzida por complexos de rutênio II e III em diferentes linhagens tumorais - Pereira, Flavia de Castro (2014)
The resistance acquired by some tumor cell lines retricts the use of drugs made of platinum because of Ruthenium compounds have been objects of great attention for presenting antimetastatic properties and low toxicity. Ruthenium compounds form compounds with the most different chemical binders, presenting good behavior and expanding the possibilities offor biological applications. A wide variety of coordination has enabled studies on ruthenium complexes, andseveral oxidation stages (Ru (II), Ru (III), and Ru (IV)) under physiological conditions and the rate of binder substitution. This study ranges the citotoxic activity of ruthenium (III) compound cis- Tetraammine(oxalato)Ruthenium(III) Dithionate - {Cis-[Ru(C2O4)(NH3)4]2(S2O6)} to treat human erythroleukemia (K562) tumor cell lineand the complex of ruthenium (II) coordinated a phosphine ligand and nitrile front tumor lineage S180 through the techniques of assay cell viability, assay kinetics of cell cycle phases, annexin V assay/ propidium iodide, test of mitochondrial membrane potential, test comet and gene expression through real time PCR. Both antiproliferative and cytotoxic activity revealed that K562 cells cultured with ruthenium (III) compound showed meaningful decrease in proliferation. Ruthenium(III) compound induced the IC50 value was of 18.28 μM set againts the cell cycle profiles cells not treated. Flow cytometric analysis indicated a sub-G1 arresting effect of ruthenium compound on K562 cells. Through the cell viability assay through MTT reduction technique, it was found that the complex of ruthenium (II) phosphine coordinated and nitrile presented cytotoxic activity when facing the tumor strain S180 with IC50 17.02±8.21μM and IC50 de 53.73 ± 5.71 μM for lymphocyte. When analyzing the cell cycle of tumor cells S180 treated with complex of ruthenium (II) caused increase in cells in G0/G1 and in S phase decreased. We observed an increase G2 / M. In the analysis of apoptosis assays, the results pointed that the complex ruthenium (II) induced cell death via apoptosis in tumor strain S180 as proved the increase in annexin cells V positive, depolarization of the mitochondrial membrane potential, activation of caspase 3 (Casp3) and 8 (Casp8) and increased expression levels of caspase-3 (Casp3) (mRNA), Bax (mRNA) and Tp53. The results lead to the conclusion that both complexes of ruthenium (II) and (III) induce cytotoxic activity against cell models tested, and that this activity correlates with alterations in cell cycle phases and induction of cell death via apoptosis.